Espaços friccionais: contato-improvisação como inspiração e locus dialógico na formação [in-comum] de professoras da educação básica - Pacheco, Débora Matiuzzi (2023)
This research approaches body contact as a possibility for dialogue between groups of Basic Education teachers, who teach different subjects, and, in this way, problematizes issues of a relational and pedagogical nature. The main objective of this research was: to understand the way in which body contact, through the practice of Contact-Improvisation, can be a problematizing device for the teaching practice of teachers in the education system. For that matter, the specific objectives of this study included: providing groups of teachers from the education network in the city of Balneário Camboriú-SC a space to experiment aspects of the practice of ContactImprovisation; promote debates about issues that permeate teaching activity and that arose from the moment of CI practice; analyze possible reverberations of this exchange space in the teaching activities of the participants who were part of the practice groups and with this, then analyze possible reverberations of this space of exchange in the teaching activities of the participants who were part of the practice groups and with this, then reflect, in a theoretical-practical way, on teaching, based on contact and dialogue between bodies. Regarding Methodology, this research, with a qualitative approach, is inspired by a case study, using mixed data production instruments, among which observation and direct participation stand out. The data production of the current study is carried out focusing on dialogue through the body – during training courses – as an emergence point of possible questions pertinent to the world of teaching. In order to achieve a more precise and refined understanding of the various elements of the research, which focused on the development of an [uncommon] training proposal for teachers, the following authors are taken as theoretical operators: Elyse Lamm Pineau (2010), Fernanda Carvalho Leite (2005), Giorgio Agamben (2018), Marcelo de Andrade Pereira (2017), Gilberto Icle (2010, 2011), Steve Paxton ( 1975), José Gil (2004), Marcia Berselli (2015), Sandra Meyer Nunes (2009), Byung-chul Han (2015), Paulo Freire (1967, 2005), Bell Hooks (2013), Maria Falkembach (2019), among others. It was concluded that this study was able to contribute to the educational, artistic and body studies field, being able to offer a space for discoveries and relevant reflections on the body, dialogue and teaching. In this sense, one of the main results, among others, the observation – which emerged precisely from the research participants – that the school is still a space that provides few conditions for the experience of the body in relation/dialogue as a space of knowledge production.